FORAMINIFERA DISTRIBUTION AS AN INDICATOR OF PALEOCEANOGRAPHY IN WAIPOGA WATERS, NORTHERN PAPUA - Wijaya, Joleen Felicia; Jatiningrum, Resti Samyati; Gustiantini, Luli; Putri, Mardhatillah Kurnia; Firdaus, Yulinar (BULLETIN OF THE MARINE GEOLOGY, 2025)
Foraminifera are widely used as indicators for reconstructing past marine environmental conditions. This study aims to investigate the ecological conditions of Waipoga waters, North Papua, by analyzing the distribution of foraminifera during the late Middle Holocene to Late Holocene. The study area plays an important role in the dynamics of the Indonesian Throughflow (ITF/ITF) and ENSO. Sediment core samples were prepared and identified for foraminifera, followed by quantitative analyses including relative abundance, P/B ratio, and ecological indices. In addition, sortable silt analysis was applied as an environmental proxy to support the reconstruction of past environmental changes. The results show that foraminiferal abundance throughout the sediment core varies. Planktonic foraminifera are more dominant, comprising 12 genera with 22 species. The most dominant species are Globigerinoides ruber (41,7%), Neogloboquadrina dutertrei (11%), Neogloboquadrina incompta (13,2%), Pulleniatina obliquiloculata (4%), Hastigerina pelagica (6,65%), and Globigerinoides immaturus (6,7%). Meanwhile, benthic foraminifera consist of 42 genera with 62 species, dominated by Bulimina marginata (1,8%), Cibicidoides pachyderma (1,89%), and Lenticulina calcar (1,3%). During the late Middle Holocene to Late Holocene, the Waipoga waters were influenced by variations in bottom current intensity and thermocline stability. Zones I and III reflect oligotrophic conditions with weak circulation, while Zone II indicates increased bottom current intensity, high productivity, and dysoxic conditions, suggesting possible intensification of upwelling events.